Absorptive Microstrip-Fed Slot Antenna With Wide Reflectionless Band by Loading Bandstop Filter - Yanqun Liu (IEEE, 2021)
This paper presents an absorptive microstrip-fed slot antenna with a wide reflectionless band and high radiation efficiency. The proposed antenna consists of a microstrip-fed slot antenna, a quarter-wavelength coupled-line bandstop filter (BSF), and absorptive resistors attached to a grounding pad. The BSF and absorptive resistors are connected to the end of the microstrip feedline. The slot antenna and the BSF are designed to work at the same frequency. In the working band, the high input impedance of the BSF exactly matches the slot antenna for effective radiation. While out of the working band, since the input impedance looking towards the end of the slot antenna matches well with that of the BSF, the energy will flow through the BSF and then be absorbed by the absorptive resistors. In this way, the energy both in and out of the working band will not be reflected back to the input port, which presents a wide reflectionless band. To demonstrate this idea, a prototype operating at 3 GHz is designed, fabricated, and measured. The measurements show that the proposed antenna is well matched ( $|S_{11}|< -10$ dB) in a wide frequency band from DC to 5.3 GHz, the 3-dB gain bandwidth covers from 2.85 GHz to 3.24 GHz with a peak gain of 4.54 dBi, the peak radiation efficiency can reach 93%, and a bidirectional radiation pattern is realized with more than 20 dB cross-polarization suppression in main radiation directions.